The social publicist at the convergence of Well Living and the SDGs - González-Cabrera, Catalina (2017)
Social advertising is an essential resource in the success of the goals and scopes of Well Living and, therefore, of the Sustainable Development Goals 2030. This paper analyzes its application, its meaning and how its efficacy could be achieved and confirmed. To this end, we present here cases in which education and entertainment, related to social communication, have achieved changes in attitudes and risk behaviors. In such cases, progress has been made in attaining development goals. Finally, we discuss the importance of having a theoretical and methodological basis that supports social campaigns and their products.